Dynamic changes of urinary microbiota in patients with bladder cancer after surgery and its clinical significance - Lang, Ye; Li, Pei; He, Ruixiang; Zhu, Bo; Wang, Guang; Li, Jiongming (Frontiers in Immunology, 2025)
Bladder cancer is one of the most common malignancies of the urogenital system, with a high incidence and mortality. The treatment of bladder cancer is diverse, with surgical treatment being the most common approach, including transurethral resection of bladder tumor and radical cystectomy. Following radical cystectomy, patients often undergo ileal neobladder reconstruction to restore urinary storage and voiding functions. However, postoperative changes in the urinary microbiota have become a major issue for bladder cancer patients. Traditionally, urine was believed to be sterile, but an increasing body of research has demonstrated the presence of a resident microbiota in urine, which is closely associated with the development of bladder diseases, postoperative complications, and patient prognosis. Dynamic changes in the urinary microbiota may lead to urinary tract infections, tumor recurrence, and other issues, severely affecting patients’ recovery and quality of life. In recent years, with the advancement of high-throughput sequencing technology, research on the urinary microbiota has deepened, particularly regarding its changes and clinical significance after bladder cancer surgery. Although studies have explored the impact of urinary microbiota on recurrence and prognosis after bladder cancer surgery, research on urinary microbiota changes following ileal neobladder reconstruction is still limited. Therefore, this review aims to summarize the latest research on the dynamic changes of urinary microbiota in bladder cancer patients postoperatively, especially focusing on changes after ileal neobladder reconstruction, providing references for clinical treatment and future research directions.